The Effect of Self-Efficacy, Achievement Motivation, and Adaptability on the Performance of Public Junior High School Teachers in Cirebon Regency - Putri Fatikasari; Ikva Diana Yesta; Edy Hartono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to explore in depth how self-efficacy, achievement motivation, and adaptability affect teacher performance, especially junior high school teachers who teach in Cirebon Regency. This study uses a quantitative method, while the total number of junior high school teacher participants in Cirebon Regency who participated in this study was 125. The technique used in this study is the saturated sampling technique, namely, when the size of the research population is small. This study succeeded in finding that there is a significant relationship between self-efficacy, achievement motivation, and adaptability to teacher performance. This study succeeded in showing that teacher performance is significantly influenced by three main variables, self-efficacy, achievement motivation, and adaptability, directly or indirectly. This study found that in the end, the performance of junior high school teachers in Cirebon Regency was also influenced by self-efficacy, achievement motivation, and adaptability simultaneously, which is in accordance with the results of the study of these factors.